2004
DOI: 10.1158/1078-0432.ccr-04-0265
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Interleukin 12 with Trastuzumab in Patients with Human Epidermal Growth Factor Receptor-2-Overexpressing Malignancies

Abstract: Purpose: On the basis of preclinical studies, we hypothesized that interleukin (IL)12 would potentiate the antitumor actions of an antihuman epidermal growth factor receptor-2 (HER2) monoclonal antibody (trastuzumab). We conducted a Phase I trial to determine the safety and optimal biological dose of IL-12 when given in combination with trastuzumab.Patients and Methods: Patients with metastatic HER2-positive malignancies received trastuzumab on day 1 of each weekly cycle. Beginning in week 3, patients also rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 35 publications
3
86
0
Order By: Relevance
“…However, NK cell activities of PBMCs from breast cancer patients are significantly lower compared with those of healthy individuals (53), and there is a great heterogeneity of NK cell-ADCC activity among breast cancer patients. Moreover, assessment of ADCC in metastatic breast cancer patients treated with a combination of TTZ and IL-2 or with IL-12 alone failed to find that ADCC correlates with clinical responses (54,55). Thus, transfer of immune cells stimulated to mediate a stronger ADCC represents an option to increase TTZ efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, NK cell activities of PBMCs from breast cancer patients are significantly lower compared with those of healthy individuals (53), and there is a great heterogeneity of NK cell-ADCC activity among breast cancer patients. Moreover, assessment of ADCC in metastatic breast cancer patients treated with a combination of TTZ and IL-2 or with IL-12 alone failed to find that ADCC correlates with clinical responses (54,55). Thus, transfer of immune cells stimulated to mediate a stronger ADCC represents an option to increase TTZ efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a translation of this maneuver into clinical practice has limitations because of toxicities associated with systemic administration of IL-12. 30,31 Other studies have shown an improved efficacy of FC vaccines using DCs transduced with GM-CSF 32 or IL-12/ IL-18 genes. 13 Genetic manipulation of tumor cells or DCs with CD40L has consistently enhanced their capacity to induce sustained antitumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 increased NK-cell responses to HER2-expressing breast tumor cells when used in combination with Herceptin. 113,114 IL-2 also increases ADCC activity against tumor cells for LAK cells. 115,116 IL-21 promotes the differentiation of CD56 dim CD16 1 NK-cell subset, which can potentially direct ADCC.…”
Section: Allogeneic Nk Cellsmentioning
confidence: 98%